THE PSYCHOLOGICAL SIGNIFICANCE OF PEDAGOGICAL ASSESSMENT IN THE DEVELOPMENT OF CHILDREN OF PRIMARY SCHOOL AGE - Dusmukhamedova Sh. A.; Khodjayeva Gulchehra Suratbekovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes how pedagogical assessment is a specific incentive that operates in the educational and educational activities of children of primary school age, how it determines its success and has a complex character, including a system of various incentives. The styles of communication inherent in the teacher are analyzed as one of the main factors influencing the development of the personality of a younger student. The most adequate forms of the teacher's evaluative influences, the close connection of pedagogical evaluation with the teacher's work style, as well as confirmation of its influence on the formation of the personality of a younger student are considered.